Frantz [videorecording (DVD)] - Ozon, François, 1967-; Beer, Paula, 1995-; Niney, Pierre; Stötzner, Ernst (Music Box Films, 2017)
Set in Germany and France in the immediate aftermath of the First World War (1914-1918), the film recalls the mourning period that follows great national tragedies as seen through the eyes of the war's 'lost generation': Anna, a bereft young German woman whose fiancé, Frantz, was killed during trench warfare, and Adrien, a French veteran of the war who shows up mysteriously in her town, placing flowers on Frantz's grave.